Pola Komunikasi Kelompok Pokdarwis Bua Lawah Dalam Promosi Desa Wisata Poto Tano Kabupaten Sumbawa Barat - Yohanes, Yulanda Trisula Sidarta; Khusnia, Hartin Nur; Fathullah, Asrin Dimas Tri; Wardana, Lalu Diandra Surya; Samsul, Baiq Magfira Utami; Ningrat, Ghalih Ramadhan; Listyaningrum, Novita (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze group communication activities conducted by Pokdarwis Bua Lawah in promoting Poto Tano Tourism Village. This qualitative research collected data through interviews, observations, and photo documentation. The findings reveal that group communication consists of internal and external communication. Internal communication is carried out through regular meetings but faces challenges with irregular member attendance. As an alternative, Pokdarwis utilizes WhatsApp groups for coordination. External communication follows a wheel communication model, with Pokdarwis acting as the central hub of information shared with businesses such as homestays, culinary services, and MSMEs when tourists visit. Additionally, the implementation of dual community practices shows Pokdarwis engaging local small businesses by offering tour packages and fostering a sense of ownership in the village. These findings highlight the importance of effective communication in collaboratively managing a tourism village.